Aglomeraç\~oes urbanas no Brasil e na América do sul: Trajetórias e novas configuraç\~oes - Rosa Moura; Bolívar Pêgo Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– The Urban Network and Territory research, developing in the Directory of Studies and Regional, Urban and Environmental Policies (Dirur) of the Ipea, comes following the activities focused on dynamic analysis, characterization and prospect about the urban agglomerations and the urban-regional system. With focus 2000-2014 period, highlights the changes in relations between the territories, demographic profile, productive and functional of the municipalities and their relations with the outside world, as well as in the configuration and trend of socio-spatial organization of the South American continent, in order to contribute to the development of strategies to support the formulation and implementation of territorial development policy (urban and regional) national and regional scale, In addition to subsidizing studies, research and policies of that order in scales of the subcontinent and the States of the Federation. This research is justified since over the last decade, the process of urbanization in the country and the continent have intensified. The creation of new towns, the growth of small and medium-sized cities, the population density in areas already consolidated and the occupation of pioneer fronts are some of the phenomena that characterize the ongoing process. For understanding the nature of the process of urbanization, the phenomena mentioned above need to be more clearly identified and characterized in detail, and enlarged its analysis, especially with regard to the functional role of urban centres, productive restructuring which took place (in particular the processes of industrial de-concentration and expansion of the agricultural frontier), the demographic dynamics of the cities and towns and economic infrastructure , and existing urban social-including logistic networks.
Keywords: N76; N96; O18; P25; R11; R23; R58; 330; urban network; territory; territory development; urban agglomeration; Brazil; South America